Isolation and Characterization of Mutations in Bacillus subtilis That Allow Spore Germination in the Novel Germinant d-Alanine - Paidhungat, Madan (American Society for Microbiology, 1999)
Bacillus subtilis spores break their metabolic dormancy through a process called germination. Spore germination is triggered by specific molecules called germinants, which are thought to act by binding to and stimulating spore receptors. Three homologous operons, gerA, gerB, and gerK, were previously proposed to encode germinant receptors because inactivating mutations in those genes confer a germinant-specific defect in germination. To more definitely identify genes that encode germinant receptors, we isolated mutants whose spores germinated in the novel germinant d-alanine, because such mutants would likely contain gain-of-function mutations in genes that encoded preexisting germinant receptors. Three independent mutants were isolated, and in each case the mutant phenotype was shown to result from a single dominant mutation in the gerB operon. Two of the mutations altered the gerBA gene, whereas the third affected the gerBB gene. These results suggest that gerBA and gerBB encode components of the germinant receptor. Furthermore, genetic interactions between the wild-type gerB and the mutant gerBA and gerBB alleles suggested that the germinant receptor might be a complex containing GerBA, GerBB, and probably other proteins. Thus, we propose that the gerB operon encodes at least two components of a multicomponent germinant receptor.